Biochemical characterization and ecofriendly field application of the plant growth-promoting rhizobacterium Bacillus amyloliquefaciens MH046937 isolated from Salsola imbricata in Tur Sinai, Egypt - Warda E. Ashour, Moustafa M. Zohair&, Ahmed A. El-Beih, Eman R. Hamed, Abeer A. Abd El Aty& (Journal of Applied Pharmaceutical Science, 2021)
The root-colonizing biocontrol bacterium Bacillus amyloliquefaciens was used to fight some plant root pathogens in agriculture. Bacillus amyloliquefaciens MH046937 isolated from Salsola imbricata rhizospheres was evaluated for promoting the growth of an important food legume broad bean (Vicia faba L.) in Egypt. In vitro antagonistic effect tests showed that B. amyloliquefaciens was most effective against Sclerotium rolfsii followed by Alternaria alternata. The tested strain produced a substantial quantity of indole acetic acid equivalent to 32.9 ± 0.01 µg/ml and ammonia, also synthesized hydrogen cyanide at a moderate quantity, and solubilized phosphate. The bacterial fermentation proved the capability of B. amyloliquefaciens to produce the antifungal metabolite chitinase enzyme after 48 hours which contributes to its antagonistic activities. The major compound 1 was purified and identified as 5-hydroxymethylfurfural on the basis of the Nuclear Magnetic Resonance (NMR) measurements and the Electron Ionizatio (EI) mass spectroscopy. Greenhouse application indicated that B. amyloliquefaciens (T2 ) introduced a significant increase in germination percentage from 40% to 60% and reduced the disease incidence from 1.6 to 0.4 when compared with the control pots. The obtained results showed that B. amyloliquefaciens has both direct and indirect antagonism mechanisms against soil-borne fungi, depending on its multiple physiological traits and production of chitinase enzyme.
Keywords: Rhizosphere bacteria, PGPR, Bacillus amyloliquefaciens MH046937, characterization, biocontrol, phytopathogens